Electron spin resonance of the itinerant ferromagnets LaCrGe3, CeCrGe3 and PrCrGe3. (4th October 2021) - Sichelschmidt, Jörg; Gruner, Thomas; Das, Debarchan; Hossain, Zakir
Abstract: We report electron spin resonance of the itinerant ferromagnets LaCrGe3, CeCrGe3, and PrCrGe3 . These compounds show well defined and very similar spectra of itinerant Cr 3 d spins in the paramagnetic temperature region. Upon cooling and crossing the Cr-ferromagnetic ordering (below around 90 K) strong spectral structures start to dominate the resonance spectra in a quite different manner in the three compounds. In the Ce- and Pr-compounds the resonance is only visible in the paramagnetic region whereas in the La-compound the resonance can be followed far below the ferromagnetic ordering temperature. This behavior will be discussed in terms of the specific interplay between the 4 f and 3 d magnetism which appears quite remarkable since CeCrGe3 displays heavy fermion behavior even in the magnetically ordered state.